Extracapsular cataract microsurgery and posterior chamber intraocular lenses - Buratto, Lucio; Manfredi, Bianca; Massa, Mariacristina; Rubin, Mark; Steigerwalt, Robert (Centro ambrosiano microchirurgia oculare, 1989)
The publication focuses on cataract extraction surgery and intraocular lens implantation. Intended for professional public.
Keywords: nitrooční čočky; mikrochirurgie; Microsurgery; Cataract Extraction; Lenses, Intraocular; chirurgie; extrakce katarakty; oftalmologie; implantace nitrooční čočky; Lens Implantation, Intraocular